The Influence of Customer Satisfaction, Service Quality on Financial Performance at Perumda Tirta Mayang Drinking Water, Jambi City - Rita Friyani; Wiralestari Wiralestari; Novita Ekasari (Indonesian Journal of Business Analytics, 2023)
The purpose of this study was to see the effect of Customer Satisfaction, Service Quality on the Financial Performance of Perumda Tirta Mayang Jambi City. The population in this study were all customers of Perumda Tirta Mayang, Jambi City, totaling 94,024 customers. Sampling used the Slovin formula to obtain a total sample of 100 people. Methods of data collection using a questionnaire. The data analysis method used is logistic regression analysis using the SPSS version 24 software program.